2021
DOI: 10.3389/fmolb.2021.751299
|View full text |Cite
|
Sign up to set email alerts
|

Potential Value of TNF-α (–376 G/A) Polymorphism and Cystatin C (CysC) in the Diagnosis of Sepsis Associated Acute Kidney Injury (S-AK I) and Prediction of Mortality in Critically Ill patients

Abstract: Sepsis Associated Kidney Injury represents a major health concern as it is frequently associated with increased risk of mortality and morbidity. We aimed to evaluate the potential value of TNF-α (−376 G/A) and cystatin C in the diagnosis of S-AKI and prediction of mortality in critically ill patients. This study included 200 critically ill patients and 200 healthy controls. Patients were categorized into 116 with acute septic shock and 84 with sepsis, from which 142 (71%) developed S-AKI. Genotyping of TNF-α (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Nevertheless, serum cystatin C was able to predict the occurrence of AKI, one to two days earlier than serum Cr (18,25). Cystatin C has been suggested as a potential predictor for the early diagnosis of S-AKI or was an alternative to the gold standard "creatinine" in growing number of studies in recent years (18,26). Regardless of the underlying precipitating factors, previous studies have demonstrated that cystatin C played a significant role in the diagnosis and prediction of kidney injury in sepsis or other critical clinical conditions (25, 27).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Nevertheless, serum cystatin C was able to predict the occurrence of AKI, one to two days earlier than serum Cr (18,25). Cystatin C has been suggested as a potential predictor for the early diagnosis of S-AKI or was an alternative to the gold standard "creatinine" in growing number of studies in recent years (18,26). Regardless of the underlying precipitating factors, previous studies have demonstrated that cystatin C played a significant role in the diagnosis and prediction of kidney injury in sepsis or other critical clinical conditions (25, 27).…”
Section: Discussionmentioning
confidence: 93%
“…It is not significantly influenced by biological factors such as age, gender, muscle mass, diet, infection, and tumors, in contrast to Creatinine (Cr). Serum Cr may not be able to detect very early changes in renal function, particularly in sepsis patients with early tubular necrosis (18). Nevertheless, serum cystatin C was able to predict the occurrence of AKI, one to two days earlier than serum Cr (18,25).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“… 40 Moreover, increasing studies have indicated that cystatin C was a potential predictor for the early diagnosis of S-AKI or was an alternate to the gold standard “creatinine” due to its considerable stability. 41 , 42 However, no research has been conducted to determine whether the combination of inflammation and coagulation indicators can be used to predict patients with S-AKI. In our present study, we discovered that model 3 (constructed with PCT, PLT, and PTA) (AUC = 0.855) exhibited more predictive value than either Cr (AUC = 0.807) or cystatin C (AUC = 0.765) in sepsis patients of the training cohort.…”
Section: Discussionmentioning
confidence: 99%